A Novel Splice Site Mutation in IFNGR2 in Patients With Primary Immunodeficiency Exhibiting Susceptibility to Mycobacterial Diseases - Bandari, Aravind K.; Muthusamy, Babylakshmi; Bhat, Sunil; Govindaraj, Periyasamy; Rajagopalan, Pavithra; Dalvi, Aparna; Shankar, Siddharth; Raja, Remya; Reddy, Kavita S.; Madkaikar, Manisha; Pandey, Akhilesh (Frontiers in Immunology, 2019)
Primary immunodeficiency (PID) refers to a group of heterogeneous genetic disorders with a weakened immune system. Mendelian susceptibility to mycobacterial disease (MSMD) is a subset of PID in which patients exhibit defects in intrinsic and innate immunity. It is a rare congenital disorder characterized by severe and recurrent infections caused by weakly virulent mycobacteria or other environmental mycobacteria. Any delay in definitive diagnosis poses a major concern due to the confounding nature of infections and immune deficiencies. Here, we report the clinical, immunological, and genetic characteristics of two siblings (infants) with recurrent infections. There was a history of death of two other siblings in the family after BCG vaccination. Whole exome sequencing of the two affected surviving infants along with their consanguineous parents identified a novel, homozygous single nucleotide splice acceptor site variant in intron 2 of the interferon gamma receptor 2 (IFNGR2) gene. Sanger sequencing of DNA obtained from blood and fibroblasts confirmed the variant. The patients underwent bone marrow transplantation from their father as a donor. RT-PCR and Sanger sequencing of the cDNA of patients from blood samples after transplantation showed the expression of both wild type and mutant transcript expression of IFNGR2. To assess partial or complete expression of IFNGR2 mutant transcripts, fibroblasts were cultured from skin biopsies. RT-PCR and Sanger sequencing of cDNA obtained from patient fibroblasts revealed complete expression of mutant allele and acquisition of a cryptic splice acceptor site in exon 3 that resulted in deletion of 9 nucleotides in exon 3. This led to an in-frame deletion of three amino acids p.(Thr70-Ser72) located in a fibronectin type III (FN3) domain in the extracellular region of IFNGR2. This illustrates individualized medicine enabled by next generation sequencing as identification of this mutation helped in the clinical diagnosis of MSMD in the infants as well as in choosing the most appropriate therapeutic option.